2010
DOI: 10.3923/biotech.2010.119.130
|View full text |Cite
|
Sign up to set email alerts
|

Biolistic Transformation of Citrullus vulgaris Schrad (Watermelon)

Abstract: Abstract:In this study, DNA-coated gold particles were used to transform cotyledon sections including axillary meristem of Citrullus vulgaris using the biolistic method for optimizing the transformation parameters and eventually regeneration of putative transgenic watermelon plants. Initially, five biolistic parameters namely helium pressure, macrocarrier to target tissue distance, explant ages, DNA concentrations and osmotic treatment were optimized using plasmid pRQ6 (carrying both gusA and hpt genes). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, distance of flight has a very important role in tissue damage and DNA penetration in plants. In our study, when we increased the distance of flight, the GUS transient expression levels were considerably lower than the ones observed when using 8 and 11 cm (Table 1 ); this may be due to the velocity decrease of the microcarriers that reduces the penetration force and DNA integration (Suratman et al 2010 ).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In addition, distance of flight has a very important role in tissue damage and DNA penetration in plants. In our study, when we increased the distance of flight, the GUS transient expression levels were considerably lower than the ones observed when using 8 and 11 cm (Table 1 ); this may be due to the velocity decrease of the microcarriers that reduces the penetration force and DNA integration (Suratman et al 2010 ).…”
Section: Discussionmentioning
confidence: 49%
“…The type and concentration of the osmotic agent may increase the transient gene expression by reducing the turgor pressure in cells, helping to increase the survival probability of the cells by avoiding cell rupture after the blast generated from the bombardment (Rosillo et al 2003). The positive effect of using mannitol and combinations with sorbitol has already been reported in plant systems such as watermelon (Suratman et al 2010) and coffee (Gatica et al 2009). Even though the use of mannitol generated positive results in foci formation (Table 1), the sorbitol + mannitol treatment and the maltose + sorbitol + mannitol treatment did not generate any synergic effect that could enhance GUS expression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The earliest study on watermelon transformation was reported by Choi et al, they successfully obtained a transgenic watermelon plant that expresses the GUS reporter gene (Choi et al 1994). Thereafter, several delivery methods have been utilized for watermelon transformation; these methods include biolistic transformation (Suratman et al 2010) and pollen tube pathway (Chen et al 1998), with the Agrobacterium tumefaciens-mediated transformation being the predominant method. And few transgenic watermelon plants were successfully obtained, such as expression an untranslatable chimeric construct containing truncated ZYMV coat protein (CP) and PRSV W CP genes to generate ZYMV and PRSV resistence watermelon (Yu et al 2011b), expressing the yeast HAL1 gene to enhance watermelon salt tolerance (Ellul et al 2003), expressing the Cucumber green mottle mosaic virus coat protein gene (CGMMV-CP) to develop CGMMV resistance in watermelon rootstocks (Park et al 2005), and so on.…”
Section: Introductionmentioning
confidence: 99%